I'm having some trouble with this concept. Expression: 3x(4x + 5) and another one -2x(3x - 12)
Follow Math Help Forum on Facebook and Google+
Recall $\displaystyle a(b+c) = a\times b +a\times c$ Therefore $\displaystyle 2x(7x+4) = 2x\times 7x+2x\times 4 = 14x^2+8x$ and $\displaystyle -12x(6x-3) = -12x\times 6x-12x\times -3 = -72x^2+36x$ Use these examples to do yours.
$\displaystyle 3x(4x + 5)$ $\displaystyle 3x(4x) + 3x(5)$ $\displaystyle 12x^2 + 15x$ $\displaystyle -2x(3x - 12)$ $\displaystyle -2x(3x) -2x(-12)$ $\displaystyle -6x^2 + 24x$
Thanks. I have another question, what's 14x^2 + x^2? Is that 15x^2?
And 2x(x + 3) = 3x + 3? Or 2x^2 + 3?
Originally Posted by ahhlecks Thanks. I have another question, what's 14x^2 + x^2? Is that 15x^2? Yep
Originally Posted by ahhlecks And 2x(x + 3) = 3x + 3? Or 2x^2 + 3? Neither, $\displaystyle 2x(x + 3) = 2x^2 + 6x$
Thank you. This one's got me stumped. 4x^2(5x + 6) + 2x(x^2 + 10x - 12)
I got 20x^3 + 24x^2 + 4x^3 + 20x^2 - 24x = 24x^3 + 44x^2 - 24x
View Tag Cloud